A CASE OF GIANT INVASIVE MACROPROLACTINOMA PRESENTING AS A NASOPHARYNGEAL MASS - Yeh, Li Sin; Lin, Chan Pei; Sieng, Florence Tan Hui (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Giant prolactinomas are rare and can invade the surrounding structure. Invasion tends to involve the suprasellar and cavernous sinus region with a minority invading the base of the skull. CASE We describe a rare presentation of giant invasive prolactinoma masquerading as nasopharyngeal tumour. A 33-year-old female presented to the ENT clinic with nasal congestion, blocked ear, progressive right-sided hearing loss for 4 months and epistaxis and headache for 2 weeks. Nasopharyngeal scope showed a large mass protruding from the nasopharynx into the nasal cavity. Biopsy taken reported a neuroendocrine tumour with diffusely positive immunohistochemistry for synaptophysin, chromogranin and vimentin. Ki67 was 10%. MRI of the brain showed a large nasopharyngeal mass (7.1 x 9.8 x 6.3 cm) with complete obliteration of the nasopharynx and erosion of the sphenoid bone and clivus. There was also extensive multidirectional invasion of the surrounding tissue. The patient was referred to the neurosurgery and oncology team. Further history found that the patient had oligomenorrhea for many years and became amenorrhoeic past 2 years. She denied galactorrhoea. Visual field testing showed left inferior quadrantanopia. Prolactin level was 625,740 uIU/mL. She was then referred to our endocrine service. Thyroid function and 8 am cortisol were normal. Further histopathology staining showed positivity for prolactin and ACTH. She was initiated on cabergoline 0.5 mg 3x/week. She developed a CSF leak after 2 weeks; after tumour debulking and leak repair, cabergoline dose was titrated to 0.5 mg daily. Prolactin reduced to 160727 uIU/mL and the tumour size decreased to 6.0 x 8.3 x 6.0 cm. Multidisciplinary team discussion decided on a trial of higher dose cabergoline (5.5 mg/week) prior to consideration for radiotherapy; however, the patient developed another CSF leak 1 month after dose titration, requiring another repair. CONCLUSION Invasive giant prolactinoma may rarely present with skull base invasion and intranasal extension masquerading as nasopharyngeal tumor. Careful clinical evaluation is important to diagnose this rare presentation to allow timely and appropriate management.